Assessment of Regional Economic Security Level in Innovative Development - Arkhipova, Lidia S.; Kulikova, Elena I. (Journal of Reviews on Global Economics, 2020)
Analysis of the innovative development of the regional economy is a relevant problem due to its role in ensuring the economic security of the country and achieving priority goals. The subject of the research are the regions of one of Russia’s most dynamically developing macro-regions â€“ the Volga Federal District. It features innovation clusters, a network of modern manufacturing companies, research organizations. At the same time, it developed a significant territorial heterogeneity of the regional space. Therefore, in the course of the study, a typology of the regions was drafted according to a number of indicators, which made it possible to assess the level of their innovative development and identify zones of relative stability, medium and critical state. A forecast of the main indicators of the innovation component was made showing the ability of the regions to overcome the factors preventing the development of the innovation economy. The research results showed that most of the regions have a medium level of economic security in the field of innovation. The Nizhny Novgorod Region and the Republic of Tatarstan are at a high level. The economy of these regions is characterized by a high level of diversification, resilience to instability in the domestic market and external challenges. The Saratov region, the Republic of Mari El and the Orenburg Region are in a low-level zone. A short-term forecast indicates that in general the situation will not change â€“ the regions will increase or decrease the values of the indices within the achieved levels of economic security. A qualitative transition to a new level is possible provided that the problems that hinder the innovative economy in the regions are eliminated.